Perbandingan kejadian post partum blues pada ibu post partum Dengan persalinan normal dan sectio caesarea - Andrew Umaya Miyansaski; Misrawati - -; Febriana - Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
childbirth and section caesarea. This research used comparative study design with cross sectional. Research has been done in outpatient of obstetric of mother and child hospital Andini in Pekanbaru on 56 post partum mothers which was chosen by using purposive sampling technique by considering inclusion criteria. Measurement tools that has been used is questionnaire of Edinburgh Postnatal Depression Scale (EPDS) that has been tested with validity and reliability test. Analysis that was used is bivariate analysis with Chi-Square test. Result of this research has shown that 50% of total sampel with normal childbirth and occurring post partum blues are 32,1%, while another childbirth with section caesarea are 35,7% then obstained the p value (0,778) > α (0,05). Conclusion of this research is there is no differences of post partum blues incidence in post partum mothers with normal childbirth and section caesarea. According to this research, the hospital are expected to increase preventive efforts to prevent the occurrence of post partum blues by providing health education when antenatal visit in order to screening of post partum blues to the all of post partum mothers. Keywords: normal childbirth, post partum blues, post partum mothers, section caesarea